2020
DOI: 10.1136/heartjnl-2020-317870
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring indirect impact of COVID-19 pandemic on services for cardiovascular diseases in the UK

Abstract: ObjectiveTo monitor hospital activity for presentation, diagnosis and treatment of cardiovascular diseases during the COVID-19) pandemic to inform on indirect effects.MethodsRetrospective serial cross-sectional study in nine UK hospitals using hospital activity data from 28 October 2019 (pre-COVID-19) to 10 May 2020 (pre-easing of lockdown) and for the same weeks during 2018–2019. We analysed aggregate data for selected cardiovascular diseases before and during the epidemic. We produced an online visualisation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 22 publications
4
111
1
2
Order By: Relevance
“…Regarding stroke, access to acute stroke diagnostics and time-dependent therapies was limited or delayed owing to reduced emergency service capacities, and a marked reduction in the number of patients admitted with transient ischemic attack and/or stroke was noted in the emergency departments of three European countries (Italy, France, and Germany)[ 5 ]. Another study in the United Kingdom showed similar findings, whereby substantial reductions in the activities of patients with cardiac, cerebrovascular, and other vascular complications started 1–2 weeks before the lockdown and dropped to 31–88% following the lockdown [ 6 ]. All of these may be attributed to a major burden of the collateral effects of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 75%
“…Regarding stroke, access to acute stroke diagnostics and time-dependent therapies was limited or delayed owing to reduced emergency service capacities, and a marked reduction in the number of patients admitted with transient ischemic attack and/or stroke was noted in the emergency departments of three European countries (Italy, France, and Germany)[ 5 ]. Another study in the United Kingdom showed similar findings, whereby substantial reductions in the activities of patients with cardiac, cerebrovascular, and other vascular complications started 1–2 weeks before the lockdown and dropped to 31–88% following the lockdown [ 6 ]. All of these may be attributed to a major burden of the collateral effects of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 75%
“…4 Ball et al tracked disruptions in acute cardiovascular services across nine UK hospitals. 5 Taken together, these two studies quantify what many readers of this Journal have experienced firsthand: the restructuring of hospital services to cope with an influx of COVID-19 cases, combined with social distancing measures, has severely limited access to cardiovascular care, adversely impacting patient outcomes.…”
Section: Covid-19 Threatens To Derail Progress On Cardiovascular Healmentioning
confidence: 98%
“…Although Ball et al did not attempt to link reduced service delivery to mortality outcomes, other studies from the UK have estimated excess cardiovascular deaths during COVID-19. 5 Brant et al posited that excess cardiovascular mortality in Brazil was partly due to avoidance of care (ie, increases cardiovascular deaths occurring at home). 4 They also found that healthcare system collapse in more socioeconomically deprived states was associated with increased acute coronary syndrome and stroke deaths in these states, independent of the uptick in deaths at home.…”
Section: Covid-19 Threatens To Derail Progress On Cardiovascular Healmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiological model of serial AS progression ('aortic stenosis cascade', in blue), along with imaging biomarkers targeting each phase (red) and potential disease-modifying treatments being currently tested in randomised clinical trials (green). 1 South Korean PCSK9 inhibitors (NCT03051360); 2 EAVaLL: early aortic valve lipoprotein(a) lowering (NCT02109614); 3 SALTIRE II: study investigating the effect of drugs used to treat osteoporosis on the progression of calcific aortic stenosis (NCT02132026); 4 BASIK2: bicuspid aortic valve stenosis and the effect of vitamin K 2 on calcium metabolism on 18F-NaF PET/MRI (NCT02917525); 5 EvoLVeD: early valve replacement guided by biomarkers of left ventricular decompensation in asymptomatic patients with severe AS (NCT03094143); 6 Early TAVR: evaluation of transcatheter aortic valve replacement compared with surveillance for patients with asymptomatic severe aortic stenosis (NCT03042104). 18F-FDG, 18-fluorodeoxyglucose; 18F-NaF, 18-sodium fluoride; AS, aortic stenosis; AVC, aortic valve calcification; PET, positron emission tomography; PCSK9, proprotein convertase subtilisin/kexin type 9; TAVR, transcatheter aortic valve replacement.…”
Section: Patient Consent For Publication Not Requiredmentioning
confidence: 99%